Discussions on the Architecture and Functions of Shanghai Metro Automatic Fare Collection System under Electromechanical System Digital Transformation - DONG Xiaoting (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] In the planning and practice of digital transformation of urban rail transit electromechanical system in various cities, it is necessary to carry out architecture reconstruction and functional redefinition for automatic fare collection system (hereinafter abbreviated as AFC) to adapt to digital transformation. [Method] Based on the guidance on the construction of the Shanghai Metro electromechanical system, a cloud edge three-layer architecture for the on-site layer, station layer, and network layer is proposed. Combined with the current practice of Shanghai Metro AFC connected to the station digital operation platform, a two-layer architecture system of Shanghai Metro AFC center layer and equipment terminal layer is proposed on the basis of conventional automatic ticketing system architecture. The functions of the two-layer architecture are redefined, and the network composition between each layer is introduced. [Result & Conclusion] After the reconstruction of Shanghai Metro AFC, a direct network connection is adopted between the two layers of the system architecture, to adapt to the business characteristics of the AFC system. The terminal equipment layer is connected to the station digital operation system to meet the integration requirements of the station daily electromechanical system management, and the service functions in the station digital operation platform are also clarified. The restructured system architecture adapts to the changes brought by digital transformation, combines system business with operational management under digital transformation, resulting in simplified management hierarchy and reduced construction investment.